Multibody Dynamics Models of Railway Vehicle Using Adams/Rail - ABDULLAH, Mohd Azman; Ibrahim, Azhar; Hudha, Khisbullah (Scientific.Net Materials Science and Engineering, 2013)
This research is focusing on multibody dynamics modeling data and parameter comparison. The comfort and stability of railway vehicle suspension can be measured by using Ride Index Machine and other sensors. Complete model of EMU82 from KTMB is adapted to multibody software, ADAMS/Rail. With ADAMS/Rail, the behavior and characteristic of each suspension element can be determined. The accuracy of the simulation model is verified by comparing the result of body roll angle in Adams/Rail and the actual test. As for the experiment, certain test track will be chosen and simulated in ADAMS/Rail. The selection of track is based on the design and curvature characteristic. In experiment, data of roll angle and lateral acceleration are necessary. For that purpose selected sensors such as tri-axis accelerometer and gyro will be used. The running performance of the KTMB EMU82 suspension will be gathered from the simulation.